The influence of an anesthesiologist’s postoperative visit on patient satisfaction with anesthesia for the reconstruction of the anterior cruciate knee ligament - Tubić, Teodora; Mihajlović, Dunja; Petrović, Jelica; Vicković, Sanja; Nikolić, Jelena; Dolinaj, Vladimir; Andjelić, Nada (Vojnosanitetski pregled, 2022)
Background/Aim. When it comes to anesthesia, patient satisfaction (PS) is more difficult to assess than in any other medical specialty. The aim of this study was to construct a tool for assessing PS with anesthesia and then examine the effects of postoperative care provided by anesthesiologists on PS. Methods. The study included patients undergoing general anesthesia due to the reconstruction of the anterior cruciate knee ligament who were considered the American Society of Anesthesiologists (ASA) 1 and ASA 2 classes. Patients were divided into three groups: group 1 included 74 patients who had a postoperative visit performed by an attending anesthesiologist; group 2 included 70 patients who had a postoperative visit performed by a nurse anesthetist after surgery; group 3 included 74 patients who did not have postoperative visit during postoperative care by an anesthesiologist nor a nurse anesthetist. The tools used in the research were the Anesthesia Patient Satisfaction questionnaire specially designed for this study and the Post Anesthetic Recovery Scoring System (PAS). ANOVA and Pearson’s correlation coefficient were used to estimate the statistical significance of the obtained results between the groups. Results. Association between an objective assessment of the postoperative status of patients on day zero and satisfaction with the anesthesiologist’s patient management showed statistical significance (p < 0.05). Patients who had a postoperative visit by an anesthesiologist tolerated better preoperative and postoperative physical symptoms. Patients visited by an anesthesiologist were most satisfied with postoperative care (p < 0.05). Conclusion. The use of a highly reliable questionnaire for the evaluation of PS with anesthesia could improve the postoperative condition of patients and enable faster recovery during the postoperative period.
Keywords: anesthesiology; health personnel; patient satisfaction; postoperative care; surveys and questionnaires.